Relapsed refractory multiple myeloma with CNS involvement successfully treated with Elranatamab: first reported case - Mutlu, Yasa Gul; Yıgıt Kaya, Sureyya; Maral, Senem; Melek, Elif; Baslar, Zafer; Kaynar, Leylagul; Sevindik, Omur Gokmen (Frontiers in Immunology, 2023)
Central nervous system (CNS) involvement in multiple myeloma (MM) is a rare and challenging complication associated with poor prognosis and limited treatment options.Emerging T-cell directing therapies, such as bispecific antibodies (bsAbs) and chimeric antigen receptor T cells (CAR-T), have shown remarkable success in treating MM, but their efficacy in CNS involvement remains unclear. Elranatamab, a humanized bispecific antibody targeting Bcell maturation antigen (BCMA) and CD3-expressing T cells, has demonstrated promising results in relapsed refractory MM. However, its efficacy in treating CNS-MM has not been reported. We present a case of a 37-year-old male MM patient with CNS involvement who has been successfully treated with Elranatamab.